Revisiting the Evidence for the Reuse of Enteral Feeding Equipment in Ambulatory Patients: A Systematic Review. (10th September 2020) - Osland, Emma J.; Andersen, Sarah; Coleman, Emma; Marshall, Belinda
Abstract: Background: The reuse of enteral tube feeding (ETF) equipment is not recommended due to the risk of microbial contamination and subsequent risk of infection; however, this practice continues in many ambulatory settings. A systematic review of the literature was undertaken to review the evidence underpinning the cleaning and reuse of ETF equipment. Methods: Studies that investigated the reuse, decontamination, and/or cleaning of ETF equipment were considered for inclusion. Electronic databases were searched (no limits were placed on date of publication, age, or duration of reuse). Extracted data were assessed using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) and reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses recommendations. Results: Ten studies met inclusion criteria: 3 investigated changes to clinical outcomes with extending reuse from 24 to ≤72 hours using water rinses; 5 considered the efficacy of various cleaning methods assessed in laboratory conditions; 2 used a combination of both approaches. Sufficient data to allow GRADE assessment was found only for bottle‐type containers. Conclusions: A very low level of evidence supports the cleaning and reuse of rigid and "unspecified" bottle containers; no studies were found to inform the reuse of syringes used for bolus feeding or any equipment used for water infusion or flushes. There is an absence of literature evaluating the safety and clinical outcomes of cleaning and reusing ETF equipment, and research is required to support equipment reuse.